Resilience building among Chinese family caregivers of older people with Parkinson's disease in Shanghai. (14th December 2021) - Zhong, Xiaohui; Song, Priscilla P.; Wang, Zhe; Chen, Honglin
Abstract: Despite a rapid increase in people with Parkinson's disease (PD) in China, studies focusing on caregiver burden remain scarce. Challenges faced by caregivers in other Asian societies are also underexplored in the PD‐related research field. To addresses this gap, this study drew on the theory of resilience and examined the caregiving experiences of Chinese family caregivers for older people with PD. We conducted participant observation and semi‐structured interviews with 15 family caregivers of older people with PD in Shanghai in 2018. We used thematic analysis to identify key patterns of stressors and factors affecting the capacity of caregivers to address burdens. Our analysis shows that stressors faced by Chinese PD caregivers included physical limitations, psychological and emotional problems, reduction in social connections, financial burden and lack of information and knowledge. Three levels of factors—personal, social and structural—played different roles in resilience among Chinese PD caregivers. However, resilience was unevenly developed among PD caregivers across gender, kinship, residential status and generation. Our study provides novel empirical evidence about the burden on Chinese PD caregivers. It can inform policymakers and social workers as they develop a holistic understanding of promoting resilience building in this rapidly growing group. Our study also enriches cross‐cultural knowledge about factors contributing to caregivers' resilience building in Asian societies.